Home Visitation and Its Effects on Learners Behavior at Mabini District, Bohol - Saavedra, Marilow (Journal of Research and Investigation in Education, 2024)
The objective of this study is to evaluate the effects of home visitation on learner’s behavior in Abaca Elementary School in Mabini, Bohol. The subjects of the study were the kindergarten pupils of the said schools and evaluations focusing on the learner’s manifested behaviors were collected based on their respective parent’s perception and observations throughout the whole three quarters of the school year. The samples were clustered in to two groups: first group with no home visitation applied and the second group where home visitation was employed. Applying appropriate statistical treatments on the data collected, home visitation was found to have a significantly positive effect on the development and progress of the behavior of the learners as compared to the learner’s where home visitation was not employed. It was recommended that a fairly adequate and regular home visitation must be executed by teachers in every alternate quarter within the school year. A firming parent behavior also is contributor to the success of the whole visit conduct and facilitates the easier flow of the planned activities. Collaborative procedures are executed to ensure that all measures taken in this research yields benefits for the improvement of the learner’s behavior and greater chances of decreasing the misbehavior being exhibit by this learner. At the last part of this paper, a proposed home visitation module was also developed and formulated.